1975
DOI: 10.1126/science.1145193
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as Inhibitors of Lens Aldose Reductase

Abstract: Flavonoids are effective inhibitors of lens aldose reductase. Quercetin, quercitrin, and myricitrin are significantly more potent than the previously known aldose reductase inhibitors. The inhibitory activity is of the noncompetitive type. In addition, quercitrin effectively blocks polyol accumulation in intact rat lenses incubated in medium containing high concentration of sugars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
2

Year Published

1977
1977
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(67 citation statements)
references
References 7 publications
2
61
0
2
Order By: Relevance
“…Since the mid.-1970's, several studies on the inhibition of aldose reductase by flavonoids have been reported. [14][15][16] However, their structure-activity relationships were not discussed satisfactorily because of the limited number of compounds. In the present study, 94 flavonoids and stilbenes were examined to clarify the further structural requirements of flavonoids for aldose reductase inhibitory activity.…”
mentioning
confidence: 99%
“…Since the mid.-1970's, several studies on the inhibition of aldose reductase by flavonoids have been reported. [14][15][16] However, their structure-activity relationships were not discussed satisfactorily because of the limited number of compounds. In the present study, 94 flavonoids and stilbenes were examined to clarify the further structural requirements of flavonoids for aldose reductase inhibitory activity.…”
mentioning
confidence: 99%
“…Scopoletin has also been reported to exhibit moderate ARI activity [25]. Quercetin, a flavonoid that is commonly distributed in the flowers of different plant species, is widely-reported to exhibit strong antioxidant activity and ARI effects [8]. Hence, these compounds were analyzed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…For example, flavonoids, a class of polyphenolic compounds, are known to exhibit a variety of biological activities [7]. Particularly, quercetin, a flavonoid ubiquitously found in many flowers, is known to have strong inhibitory effects against AR [8].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the type of inhibition by these flavonoids is noncompetitive, a factor preferable in therapeutic use over competitive inhibitors. 27,28) Furthermore, previous studies indicate that common feature of aldose reductase inhibitors is a hydrophobic region attached to an acid group. The flavonoids meet these requirements.…”
Section: Chemicalsmentioning
confidence: 99%